Gamma oscillations in the hippocampus require high complex I gene expression and strong functional performance of mitochondria - Kann, Oliver; Huchzermeyer, Christine; Kovács, Richard; Wirtz, Stefanie; Schuelke, Markus (Brain, 2011)
Fast neuronal network oscillations in the gamma range (∼30-90 Hz) have been implicated in complex brain functions such as sensory processing, memory formation and, perhaps, consciousness, and appear to be exceptionally vulnerable to various pathologies. However, both energy demand and mitochondrial performance underlying gamma oscillations are unknown. We investigated the fundamental relationship between acetylcholine-induced gamma oscillations, mitochondrial gene expression and oxidative metabolism in hippocampal slice preparations of mouse and rat by applying electrophysiology, in situ hybridization, quantitative polymerase chain reaction, oxygen sensor microelectrode (interstitial partial oxygen pressure) and imaging of mitochondrial redox state [nicotinamide adenine dinucleotide (phosphate) and flavin adenine dinucleotide fluorescence]. We show that (i) gamma oscillation power, oxygen consumption and expression of complex I (nicotinamide adenine dinucleotide:ubiquinone oxidoreductase) subunits are higher in hippocampal subfield CA3 than in CA1 and dentate gyrus; (ii) the amount of oxygen consumption of gamma oscillations reaches that of seizure-like events; (iii) gamma oscillations are exquisitely sensitive to pharmacological complex I inhibition; and (iv) gamma oscillations utilize mitochondrial oxidative capacity near limit. These data suggest that gamma oscillations are especially energy demanding and require both high complex I expression and strong functional performance of mitochondria. Our study helps to explain the exceptional vulnerability of complex brain functions in ischaemia as well as in neurodegenerative and psychiatric disorders that are associated with mitochondrial dysfunction.
Advance access publication December 22, 2010
Gesehen am 11.07.2022